Functional analysis of the C-terminal domains of the site-specific recombinases XerC and XerD. - Ferreira, H; Butler-Cole, B; Burgin, A; Baker, R; Sherratt, D; Arciszewska, L (2003)
The tyrosine family site-specific recombinases XerC and XerD convert dimers of the Escherichia coli chromosome and many natural plasmids to monomers. The heterotetrameric recombination complex contains two molecules of XerC and two of XerD, with each recombinase mediating one pair of DNA strand exchanges. The two pairs of strand exchanges are separated in time and space. This demands that the catalytic activity of the four recombinase molecules be controlled so that only XerC or XerD is active at any given time, there being a switch in the recombinase activity state at the Holliday junction intermediate stage. Here, we analyse chimeras and deletion variants within the recombinase C-terminal domains in order to probe determinants that may be specific to either XerC or XerD, and to further understand how XerC-XerD interactions control catalysis in a recombining heterotetramer. The data confirm that the C-terminal "end" region of each recombinase plays an important role in coordinating catalysis within the XerCD heterotetramer and suggest that the interactions between the end regions of XerC and XerD and their cognate receptors within the partner recombinase are structurally and functionally different. The results support the hypothesis that the "normal" state in the heterotetrameric complex, in which XerC is catalytically active and XerD is inactive, depends on the interactions between the C-terminal end region of XerC and its receptor region within the C-terminal domain of XerD; interference with these interactions leads to a switch in the catalytic state, so that XerD is now preferentially active.